Analisis Perbandingan Moodle dan Google Classroom Menggunakan Technology Acceptance Model - Santiadi, Sherly; Majiah, Arya Tri Putra; Ruis, Nisa Deviani Agustin; Annabel, Kathleen Felicia; Karnalim, Oscar (Fakultas Teknologi Informasi, 2024)
The study aims to analyze the comparison of student acceptance levels of the Learning Management System (LMS) which are Moodle and Google Classroom using the Technology Acceptance Model (TAM) in the West Java region, Indonesia. The results of this study show that there is a difference in the level of acceptance of the two LMSs but the difference is not very significant. Moodle appears to be slightly more effective in increasing student productivity and is more commonly used in West Java due to the sample of respondents who are mostly from the Faculty of Information Technology (FIT) at Maranatha Christian University. FIT students have largely adopted the Moodle LMS implemented into the Morning Platform (Maranatha Online Learning). With more complex features, Moodle meets the needs of more experienced users. On the other hand, Google Classroom is considered easier to use, especially for students who are new to the LMS. However, over a longer period of time, Moodle maintained a slight edge in terms of usability and user satisfaction. This research makes an important contribution in understanding the preferences and needs of university students in terms of LMS usage, especially in the West Java region.